Upaya Meningkatkan Keterampilan Menulis Puisi Menggunakan Model Kooperatif Tipe Think, Talk,Write di Sekolah Dasar 2 Pekanbaru - Nurhasni Nurhasni (Jurnal Pendidikan Tuntas, 2025)
This study aims to analyze the improvement of poetry writing skills in third-grade students at SDN 2 Pekanbaru using the Think, Talk, Write (TTW) cooperative learning model. Poetry writing skills are considered difficult as they require the ability to find and use appropriate words and master vocabulary. Initial data showed that 88.24% of students had not achieved the minimum completeness criteria (KKM) score of 80 in poetry writing, and students were less enthusiastic in learning. This classroom action research (CAR) was conducted in two cycles. In Cycle I, the completion percentage increased to 64.71%. A significant improvement was observed in Cycle II, where 100% of students achieved classical completeness, although individual completeness did not always reach 100%. This success was supported by the teacher's mastery of the TTW model, the teacher's ability to create a safe and competitive learning environment, effective time management, and a good emotional connection between the teacher and students. Thus, the TTW learning model proved effective in improving students' poetry writing skills in Elementary School.